THE IMPACT OF APPLYING BLOCKCHAIN TECHNOLOGY IN ACCOUNTING AND AUDITING (World Bulletin of Management and Law, 2023)
Blockchain provides a completely new way for the brand towards documents and procedures, as well as keeping information and cash transactions. It actually has prospects towards fundamentally changing the arena of the bookkeeping profession as well as improving the business community. Within this particular short research paper, our team talks about the implications of blockchain in the bookkeeping business as well as bookkeeping. The use of blockchain can help provide clarity regarding asset ownership and the existence of liabilities, and can significantly increase the efficiency of an accountant. Blockchain provides the possibility of accounting and auditing. Blockchain helps auditors keep track of the account. Blockchain technology has conducted for auditors the audit traces they follow. For an accountant, blockchain helps in matchmaking, tracking asset ownership, and authenticating transactions through the features found in the technology. Blockchain can be used as a source to verify the data reported by accountants to users of the information generated by accounting. With blockchain technology, which has emerged to call into question the need for intermediary institutions that provide trust and to show that there is no need to trust intermediary institutions, it is expected that many sectors from the banking, financial, logistics and supply chain sector to the health sector will be affected, especially cost and time savings. As the number of blockchain technologies increases, the current risks persist and the new technology brings new risks. This technology inevitably affects audit activities as it does in all sectors. Companies must identify these risks and take precautions. Internal audit departments should develop themselves on blockchain, and companies should allocate an additional budget to workers in this department and ensure that they receive training in the subject